Menelusuri Peran Profisiensi Bahasa Inggris Dalam Sistem Informasi Akuntansi Dalam Pelaporan Keuangan Global - Ujang Kusnaedi; Hajarudin Hajarudin (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This study aims to explore the role of English proficiency in accounting information systems, as well as its implications for global financial reporting. The study was conducted for one month in January 2024 at STIE Ganesha, involving 20 college students. The research method used is a qualitative approach, with data collection through interviews and observation. The findings show that English proficiency has a significant impact on the use of accounting information systems and understanding of global financial reporting. The implications of this study emphasize the importance of developing English language skills among accounting students and professionals to improve the quality of financial reporting accessed globally. This research is important because it fills a gap in understanding of the role of English proficiency in accounting information systems for global financial reporting. The implication is that a better understanding of the relationship between English proficiency and needs in the context of accounting information systems will help prepare accounting students for more success in their careers, especially in an increasingly connected global business environment. In addition, this research can also provide new insights for educational institutions and the world of work in designing curricula and training that are more relevant and effective in preparing accounting professionals to deal with future global challenges.